Linked-read genome sequencing identifies biallelic pathogenic variants in DONSON as a novel cause of Meier-Gorlin syndrome - Knapp, Karen M; Sullivan, Rosie; Murray, Jennie; Gimenez, Gregory; Arn, Pamela; D'Souza, Precilla; Gezdirici, Alper; Wilson, William G; Jackson, Andrew P; Ferreira, Carlos; Bicknell, Louise S (Journal of medical genetics, 2020)
MaterialLinked-read whole genome sequencing (WGS) presents a new opportunity for cost-efficient singleton sequencing in place of traditional trio-based designs while generating informative-phased variants, effective for recessive disorders when parental DNA is unavailable.MethodsWe have applied linked-read WGS to identify novel causes of Meier-Gorlin syndrome (MGORS), a condition recognised by short stature, microtia and patella hypo/aplasia. There are eight genes associated with MGORS to date, all encoding essential components involved in establishing and initiating DNA replication.ResultsOur successful phasing of linked-read data led to the identification of biallelic rare variants in four individuals (24% of our cohort) in DONSON, a recently established DNA replication fork surveillance factor. The variants include five novel missense and one deep intronic variant. All were demonstrated to be deleterious to function; the missense variants all disrupted the nuclear localisation of DONSON, while the intronic variant created a novel splice site that generated an out-of-frame transcript with no residual canonical transcript produced.ConclusionVariants in DONSON have previously been associated with extreme microcephaly, short stature and limb anomalies and perinatal lethal microcephaly-micromelia syndrome. Our novel genetic findings extend the complicated spectrum of phenotypes associated with DONSON variants and promote novel hypotheses for the role of DONSON in DNA replication. While our findings reiterate that MGORS is a disorder of DNA replication, the pathophysiology is obviously complex. This successful identification of a novel disease gene for MGORS highlights the utility of linked-read WGS as a successful technology to be considered in the genetic studies of recessive conditions.